PERENCANAAN STRATEGI PENGEMBANGAN PARIWISATA DI KARATON KASUNANAN SURAKARTA HADININGRAT - Irmawati Irmawati; Dyah Lituhayu; Maesaroh Maesaroh (Journal of Public Policy and Management Review, 2013)
The aim of this research is do the analysis afterwards the condition of tourism karaton surakarta hadiningrat, do the analysis afterwards environment both internally and externally to know a factor and supporter of the development of tourism, the economy and formulate a strategy to develop tourism. Used in the analysis method of analysis training strategic environment that exists in the development of tourism. This research using a descriptive qualitative research with the use of an informant who is derived from karaton surakarta hadiningrat as the management of tourist attractions museum karaton surakarta hadiningrat, the hotels and travel bureau of tourism as well as visitors karaton surakarta hadiningrat tourist attractions.The results of research that in tourism development strategy karaton surakarta indicated that during this condition has not been maintained, tourism potential optimally the environmental condition internal and external also is good but there are still deficient, the excess there are still on the weak quality of its human resources, the absence of education for employee dept. of tourism in the region, as well as several other supporting facilities and its appendages are lacking. To do the analysis afterwards environment internal and external then obtained a factor of the economy and supporters that affects in formulating strategies which will then tested using litmus test for measuring the degree of kestrategisan program by virtue of the score that exist.Of this research, advised to strategic programs that have been formulated carried out consistently and further improved with opens up the possibility for the emergence of inovasi-inovasi positive in its implementation.